ОСОБЕННОСТИ ЛОКАЛЬНОЙ КОНЦЕНТРАЦИИ ИННОВАЦИОННОЙ АКТИВНОСТИ В КАЗАХСТАНЕ В КОНТЕКСТЕ МИРОВОГО ОПЫТА - F. M. Dnishev (Экономика: стратегия и практика, 2019)
The purpose of the article is to consider the features of the local concentration of innovative activity abroad and to show the possibilities of adapting the world experience in Kazakhstan.The methodology of the article is based on the theoretical and methodological approach to identifying the advantages of geographical localization of innovation and technological activities, according to which the accumulation of skills, know-how and knowledge occurs in a spatially limited context, where a kind of favorable«industrial atmosphere» arises, that can strengthen the economic growth and stimulate the production and diffusion of technological innovation.It is shown that in the foreign practice there are different local innovative typologies: innovation clusters, learning regions, regional innovation systems, local innovation systems. The possibilities of their development in Kazakhstan are considered.